Response of germination and electrical conductivity of seeds produced by Echinacea purpurea's mother plants under the influence of biological fertilizers and drought stress - Mahmood Attarzadeh; Hamidreza Balouchi; Mohsen Movahhedi Dehnavi; amin salehi; Majid Rajaie (علوم و فناوری بذر ایران)
Reduction in germination and growth can be seen in seeds obtained from mother plants which have experienced water stress. From the other point of view utilization of biological fertilizers under environmental stress, the condition can produce seeds with higher germination capacity. This research was conducted as split plot based on a randomized complete block design with three replications in 2016. The main factor included of irrigation regimes at three levels included in soil irrigation after 25, 50 and 75% of soil moisture depletion and a sub-factor of phosphorus supply in six levels included of 100% phosphorus requirement from the source of triple superphosphate, 50% phosphorus + arbuscular mycorrhizal fungus, Mycorrhiza arbuscular fungus, 50% phosphorus + Pseudomonas fluorescens, Pseudomonas fluorescens and a control test without phosphorus fertilizer. Results showed that in 75% of soil moisture depletion, maximum amounts of germination, seed vigor, root length, stem length and seedling dry weight were obtained from 50% of phosphorus + arbuscular mycorrhiza. At irrigation level of 50 and 75% moisture depletion, the application of 50% phosphorus + arbuscular mycorrhiza made an increase in germination rate and uniformity. The electrical conductivity of Echinacea purpurea seeds showed increasing trend with intensification in drought stress. The results of this study showed that in present study Pseudomonas fluorescens had lower improvement effects on percent and rate of germination and the adjustment of drought adverse effects in compared with arbuscular mycorrhiza.